2021
DOI: 10.3389/fnut.2021.716783
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Interventions in Patients With Non-alcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis

Abstract: Background: With no approved pharmacotherapy to date, the present therapeutic cornerstone for non-alcoholic fatty liver diseases (NAFLD) is a lifestyle intervention. Guidelines endorse weight loss through dietary modifications, physical exercise, or both. However, no consensus exists on the optimal dietary treatment.Objectives: The aim of our systematic review and meta-analysis was to summarize and assess the evidence for applied types of dietary interventions on the liver and metabolic outcomes in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 80 publications
(189 reference statements)
1
60
0
3
Order By: Relevance
“…However, it is important to note that the diet without exercise did not lead to significant changes in liver enzymes, lipid profile, fasting glucose or insulin, or homeostatic assessment for insulin resistance. On the other hand, hypocaloric diet with foods high in unsaturated fatty acids significantly decreases ALT and AST, but its effects on steatosis remain to be established ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that the diet without exercise did not lead to significant changes in liver enzymes, lipid profile, fasting glucose or insulin, or homeostatic assessment for insulin resistance. On the other hand, hypocaloric diet with foods high in unsaturated fatty acids significantly decreases ALT and AST, but its effects on steatosis remain to be established ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect on liver enzymes, importantly differs among studies as some of them only showed differences within the intervention group. A novel systematic review and meta-analysis by Houttu et al [ 90 ] showed that hypocaloric diets reduce ALT levels SMD: −1.09, 95% CI: −1.49, −0.69) as well as AST levels compared to the control group (SMD: −0.75, 95% CI: −1.27, 0.23). Exercise by itself did not reduce liver enzymes, differing from the results showed by Orci et al [ 91 ] (ALT: weighted mean difference [WMD] –3.30 IU/L; 95% CI, –5.57 to –1.04; AST: WMD –4.85 IU/L; 95% CI, –8.68 to –1.02).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is one of the leading (and growing) indications for liver transplantations [39]. In recent years, it has been established that diet and the GM play an essential role in the progression of NAFLD [40,41]. Significant advances have been made linking the (gut-derived) metabolome to NAFLD and NASH.…”
Section: An Overview Of the Gut Microbiome In Cmd Perspectivementioning
confidence: 99%